Bis(Triphenylamine)Benzodifuran Chromophores: Synthesis, Electronic Properties and Application in Organic Light-Emitting Diodes - Li, Hui; Komatsu, Ryutaro; Hankache, Jihane; Sasabe, Hisahiro; Lawson Daku, Latevi Max; Özen, Bilal; Chen, Songjie; Hauser, Jürg; Hauser, Andreas; Decurtins, Silvio; Kido, Junji; Liu, Shi-Xia (Frontiers in Chemistry, 2021)
A series of bis(triphenylamine)benzodifuran chromophores have been synthesized and fully characterised. Starting from suitably functionalized benzodifuran (BDF) precursors, two triphenylamine (TPA) moieties are symmetrically coupled to a central BDF unit either at 4,8-positions through double bonds (1) and single bonds (2) respectively, or at 2,6-positions through double bonds (3). Their electronic absorption and photoluminescence properties as well as redox behaviour have been investigated in detail, indicating that the -extended conjugation via vinyl linkers in 1 and 3 leads to comparatively strong electronic interactions between the relevant redox moieties TPA and BDF. Due to intriguing electronic properties and structural planarity, 3a has been applied as a dopant emitter in organic light-emitting diodes. A yellowish-green OLED exhibits a high external quantum efficiency (EQE) of 6.2%, thus exceeding the theoretical upper limit due to energy transfer from an interface exciplex to an emissive layer.